Noninvasive MRI-Based Liver Iron Quantification: Methodic Approaches, Practical Applicability and Significance - Wunderlich, A. P.; Cario, H.; Juchems, M. S.; Beer, M.; Schmidt, S. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Due to the dependence of transverse relaxation times T2 and T2* on tissue iron content, MRI offers different options for the determination of iron concentration. These are the time-consuming spin-echo sequence as well as the gradient-echo sequence. For the latter, several data analysis approaches have been proposed, with different requirements for acquisition and post-processing: the mathematically challenging R2* analysis and the signal-intensity ratio method with its high demand on the signal homogeneity of MR images. Furthermore, special procedures currently under evaluation are presented as future prospects: quantitative susceptibility imaging, as a third approach for analyzing gradient echo data, and multi-contrast spin-echo using repeated refocusing pulses. MR theory, as far as needed for understanding the methods, is briefly depicted.Key points:• Description of underlying technology of different MRI-based procedures for liver iron quantification• Applicability of these methods in clinical practice• Validity of the methods, i. e. positive and negative predictive value, if availableCitation Format:• Wunderlich AP, Cario H, Juchems MS et al. Noninvasive MRI-Based Liver Iron Quantification: Methodic Approaches, Practical Applicability and Significance. Fortschr Röntgenstr 2016; 188: 1031 – 1036
Keywords: abdomen; MR-imaging; iron